Kinematic analysis of wrist motion during simulated colonoscopy in first-year gastroenterology fellows - Shiva K Ratuapli; Kevin C Ruff; Francisco C Ramirez; Qing Wu; Deepika Mohankumar; Marco Santello; David E Fleischer (Endoscopy International Open, 2015)
Background and study aims: Gastroenterology trainees acquire skill and proficiency in performing colonoscopies at different rates. The cause for heterogeneous competency among the trainees is unclear. Kinematic analysis of the wrist joint while performing colonoscopy can objectively assess the variation in wrist motion. Our objective was to test the hypothesis that the time spent by the trainees in extreme ranges of wrist motion will decrease as the trainees advance through the fellowship year. Subjects and methods: Five first-year gastroenterology fellows were prospectively studied at four intervals while performing simulated colonoscopies. The setting was an endoscopy simulation laboratory at a tertiary care center. Kinematic assessment of wrist motion was done using a magnetic position/orientation tracker held in place by a custom-made arm sleeve and hand glove. The main outcome measure was time spent performing each of four ranges of wrist motion (mid, center, extreme, and out) for each wrist degree of freedom (pronation/supination, flexion/extension, and adduction/abduction). Results: There were no statistically significant differences in the time spent for wrist movements across the three degrees of freedom throughout the study period. However, fellows spent significantly less time in extreme range (1.47 ± 0.34 min vs. 2.44 ± 0.34 min, P = 0.004) and center range (1.02 ± 0.34 min vs 1.9 ± 0.34 min, P = 0.01) at the end of the study compared to the baseline evaluation. The study was limited by the small number of subjects and performance of colonoscopies on a simulator rather than live patients. Conclusions: Gastroenterology trainees alter the time spent at the extreme range of wrist motion as they advance through training. Endoscopy training during the first 10 months of fellowship may have beneficial effects on learning ergonomically correct motion patterns.